Liver transplantation in patients with liver failure: Twenty years of experience from China. (16th May 2022) - Ling, Sunbin; Jiang, Guangjiang; Que, Qingyang; Xu, Shengjun; Chen, Junli; Xu, Xiao
Abstract: Liver transplantation (LT) is the only effective method of treating end‐stage liver disease, such as various types of liver failure. China has the largest number of patients with hepatitis B virus‐related disease, which is also the main cause of liver failure. From the first LT performed in 1977, and especially over the past two decades, LT has experienced rapid development as a result of continuous research and innovation in China. China performs the second‐highest number of LTs every year worldwide, and the quality of LT continues to improve. Starting January 1, 2015, all donor's livers have been from deceased donors and familial donors. Thus, China entered into a new era of LT. However, LT is still a challenging procedure in China. In this review, we introduced the brief history of LT in China, the epidemiology, aetiology and clinical outcomes of LT for liver failure in China and summarized the experience of LT from Chinese LT surgeons and scholars. The future perspectives of LT were also discussed, and it is expected that China's LT research could be further integrated elsewhere in the world.